2004
DOI: 10.1055/s-2004-813010
|View full text |Cite
|
Sign up to set email alerts
|

Höhe und Röhrenangulation als die Determinanten der möglichen Untersucher-Ortsdosisleistung in der invasiven Kardiologie

Abstract: The present experimental study on scatter radiation to the operator, as a function of body height and tube angulation, offers a representative data tool for all interventionists for use in invasive cardiology, to confirm the radiation safety of their favored coronary views, or to encourage less radiation-intensive angulations. Moreover, it provides new knowledge about special risks for crucial body regions and enables effective radiation protection strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…As shown in Figure 1 , the results showed that the operator receives the highest mean radiation dose in LAO cranial projection irrespective of the approach. This is in agreement with the reports by Kuon et al ( 9 ) and Pitney et al ( 21 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…As shown in Figure 1 , the results showed that the operator receives the highest mean radiation dose in LAO cranial projection irrespective of the approach. This is in agreement with the reports by Kuon et al ( 9 ) and Pitney et al ( 21 ).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, simultaneous measurement of the operator and patient radiation doses in different projections is of utmost importance in choosing the optimal approach. There are limited studies about the operator exposure during diagnostic coronary angiography ( 24 , 25 ), and most of our information comes from studies that have used phantom models ( 6 , 9 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be acknowledged that there is a wide range of scatter radiation at the level of the doctors' eyes due to the variability of tube position 34 and routine angles may differ between institutions or due to doctor preference. Procedures routinely utilizing steeper left anterior obliques (LAO) or LAO cranial tube angles provided in Table 3 may increase the risk of occupational exposure 17,20 . Additionally, these measurements were taken at a single point, and due to the changing nature of the X-ray scatter profile may not reflect dose levels to other areas of the head.…”
Section: Discussionmentioning
confidence: 99%